Long-term outcomes of fully covered self-expandable metal stents versus plastic stents in chronic pancreatitis - Sang Hoon Lee; Yeon Suk Kim; Eui Joo Kim; Hee Seung Lee; Jeong Youp Park; Seung Woo Park; Si Young Song; Jae Hee Cho; Seungmin Bang (Scientific Reports, 2021)
Abstract Chronic pancreatitis (CP) related main pancreatic duct (MPD) stricture has been a challenge for endoscopists. Fully covered self-expandable metal stents (FC-SEMS) has been tried in CP patients, but the efficacy and safety are still controversial. Thus, we aim to compare the long-term clinical efficacy of FC-SEMS vs. plastic stent placement in persistent MPD strictures secondary to CP. Between 2007 and 2018, 80 chronic pancreatitis patients (58 males, median age 49 years), who underwent endoscopic placement of FC-SEMS (n = 26) and plastic stent (n = 54) for persistent MPD strictures after at least 3 months of initial single plastic stenting, were retrospectively analyzed during a median follow-up duration of 33.7 months. As a result, MPD stricture resolution rate was statistically higher in FC-SEMS group (87.0% vs. 42.0%, p < 0.001). Although immediate complications occurred similarly (38.5% vs. 37.0%, p = 0.902), spontaneous migration (26.9%) and de novo strictures (23.1%) were pronounced delayed complications in FC-SEMS group. Pain relief during follow-up was significantly higher in FC-SEMS group (76.9% vs. 53.7%, p = 0.046). The total procedure cost was similar in both groups ($1,455.6 vs. $1,596.9, p = 0.486). In comparison with plastic stent, FC-SEMS placement for persistent MPD strictures had favorable long-term clinical efficacy, with its typical complications like spontaneous migration and de novo strictures.